Trends and perceptions of sustainabilty reporting and corporate governance : a case study of Eskom - Fabricius, Karin (Rhodes University, Faculty of Commerce, Investec Business School, 2004)
The King II Report on Corporate Governance was released in March 2002. This report, although focusing on South African businesses, is acclaimed as a world first in setting superior governance standards. Corporate governance in South Africa is undergoing transformation due to the influence of the King II Report, and a range of other global trends such as Global Reporting Initiative guidelines and the infamous collapse of Enron due to governance failures. Non-financial reporting (also referred to as sustainability reporting) forms the main focus of this research project. The financial reporting aspects of corporate governance, and the role of governing boards and auditors fall outside the scope of this study. Through document analysis methods, Eskom's annual reports from 1998 - 2002, were analysed to establish whether patterns in sustainability reporting were identifiable. Employees and consumers of Eskom were. interviewed, using structured interviews to explore their awareness and knowledge regarding sustainability issues. A drastic increase in Eskom's non-financial reporting was identified in 2000. Apart from the corporate governance category, none of the chosen categories showed a major change after the 2002 release of the King II Report. Possible reasons for the lack of clear trends since 2002 are that the pattern is either not yet visible or it could be speculated that Eskom, who had won various reporting awards, is a leader in the field of corporate reporting and specifically on sustainability issues. Eskom had been involved in the reviewing of the first King Report and the drawing up of the recommendations for King II, and could therefore have modified their reporting procedures in 2000, prior'to the release of King II. As shown in the trend analysis, companies are coming under increased pressure to be socially accountable and transparent. This is fast becoming a 'core business issue', illustrated by the status of the King II Report requirements for corporate governance. Even though the terminology 'sustainability reporting' is unfamiliar to employees and consumers, both groups want disclosure and transparency of sustainability issues. Employees were, however, more aware than consumers of Eskom policies regarding sustainability issues. This report recommends that companies take a pro-active approach to corporate governance and sustainability reporting, noting the desire of consumers and employees to be informed about non-financial issues. These stakeholders also need to be made more aware of the meaning and significance of sustainability reporting.
Keywords: Eskom (Firm); King Committee on Corporate Governance; Corporate governance -- South Africa; Corporation reports -- South Africa